2005
DOI: 10.1590/s0100-06832005000200011
|View full text |Cite
|
Sign up to set email alerts
|

Lodo de esgoto e sistema radicular da pupunheira

Abstract: RESUMO

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
17

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 5 publications
1
2
0
17
Order By: Relevance
“…The only treatment which did not show statistical differences when compared with T1 was T2. Similar root development was observed in the field experiment with the peach palm (Bactris gasipaes), conducted by Vega et al (2005). The authors concluded that the increase in radicular biomass was proportional to the dose of SS applied, and that with the highest doses (400 kg N ha -1 ) occurred a deepening of the radicular system and an increase in fine roots, which are responsible for absorption of most nutrients and water from the soil.…”
Section: Mf -Mineralization Fractionsupporting
confidence: 67%
See 1 more Smart Citation
“…The only treatment which did not show statistical differences when compared with T1 was T2. Similar root development was observed in the field experiment with the peach palm (Bactris gasipaes), conducted by Vega et al (2005). The authors concluded that the increase in radicular biomass was proportional to the dose of SS applied, and that with the highest doses (400 kg N ha -1 ) occurred a deepening of the radicular system and an increase in fine roots, which are responsible for absorption of most nutrients and water from the soil.…”
Section: Mf -Mineralization Fractionsupporting
confidence: 67%
“…The use of SS improves the physical properties of the soil, such as increased macro porosity and decreased micro porosity (Maria et al, 2010), and can improve root penetration and absorption of nutrients, as shown in SS application in peach palm, that showed an increase in root biomass with the increase of the applied dose (Vega et al, 2005). The knowledge of the root system is an important parameter to avoid contamination of groundwater by ions such as nitrates ) which is easily leached into the soil profile.…”
Section: Introductionmentioning
confidence: 99%
“…A porosidade total na profundidade de 0-20 cm é de 49,97 %, sendo 29,65 % de macroporos e 20,32 % de microporos (Jorge & Bovi, 1994). A densidade global do solo está em torno de 1,05 g cm -3 (Vega et al, 2005). Análises químicas, efetuadas, segundo os métodos propostos por Abreu et al (2001) e Raij & Quaggio (2001), em amostras de solo retiradas da área experimental, evidenciaram a necessidade de calagem (Quadro 1).…”
Section: Methodsunclassified
“…Houve, também nessa fase de implantação, melhoria em algumas propriedades físicas do solo, contribuindo para o aumento e o aprofundamento do sistema radicular, conforme constatado por Vega et al (2005).…”
Section: Quadro 2 Teores Foliares Médios De Macro E Micronutrientes unclassified
See 1 more Smart Citation